The role of primary cilia in thyroid diseases - Tian, Zijiao; Li, Xinlin; Yu, Xue; Yan, Shuxin; Sun, Jingwei; Ma, Wenxin; Zhu, Xiaoyun; Tang, Yang (Frontiers in Endocrinology, 2024)
Primary cilia (PC) are non-motile and microtube-based organelles protruding from the surface of almost all thyroid follicle cells. They maintain homeostasis in thyrocytes and loss of PC can result in diverse thyroid diseases. The dysfunction of structure and function of PC are found in many patients with common thyroid diseases. The alterations are associated with the cause, development, and recovery of the diseases and are regulated by PC-mediated signals. Restoring normal PC structure and function in thyrocytes is a promising therapeutic strategy to treat thyroid diseases. This review explores the function of PC in normal thyroid glands. It summarizes the pathology caused by PC alterations in thyroid cancer (TC), autoimmune thyroid diseases (AITD), hypothyroidism and thyroid nodules (TN) to provide comprehensive references for further study.